2023
DOI: 10.1111/nph.18915
|View full text |Cite
|
Sign up to set email alerts
|

Are absorptive root traits good predictors of ecosystem functioning? A test in a natural temperate forest

Abstract: Trait-based approaches provide a useful framework to predict ecosystem functions under intensifying global change. However, our current understanding of trait-functioning relationships mainly relies on aboveground traits. Belowground traits (e.g. absorptive root traits) are rarely studied although these traits are related to important plant functions.We analyzed four pairs of analogous leaf and absorptive root traits of woody plants in a temperate forest and examined how these traits are coordinated at the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…By contrast, Da et al (2023) found that the conservation gradient of absorptive root traits explained forest aboveground carbon storage and woody biomass productivity better than conservation gradients in leaves and absorptive root collaboration gradients. Although few existing studies have been restricted to absorptive fine root trait effects on tree growth, the simultaneous effects of absorptive and transport root traits have so far been unexplored.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations
“…By contrast, Da et al (2023) found that the conservation gradient of absorptive root traits explained forest aboveground carbon storage and woody biomass productivity better than conservation gradients in leaves and absorptive root collaboration gradients. Although few existing studies have been restricted to absorptive fine root trait effects on tree growth, the simultaneous effects of absorptive and transport root traits have so far been unexplored.…”
Section: Introductionmentioning
confidence: 65%
“…Shen et al (2022) showed that acquisitive leaf traits had a higher explanatory power than fine root traits for relative growth rates for height across tree species, even though SRL and RTD were significantly correlated with the relative growth rates for height of individuals. By contrast, Da et al (2023) found that the conservation gradient of absorptive root traits explained forest aboveground carbon storage and woody biomass productivity better than conservation gradients in leaves and absorptive root collaboration gradients. Although few existing studies have been restricted to absorptive fine root trait effects on tree growth, the simultaneous effects of absorptive and transport root traits have so far been unexplored.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Da et al. (2023) found that root traits emerged as more effective predictors of forest ecosystem functions compared to leaf traits. In addition, recent studies have indicated distinct responses of leaf and root traits to environmental conditions, underscoring their divergent strategies in coping with various and intricate environmental constraints (Isaac et al., 2017).…”
Section: Discussionmentioning
confidence: 99%